PENGARUH DANA PIHAK KETIGA, BI RATE, DAN BOPO TERHADAP PENYALURAN KREDIT PERBANKAN - Putri Andini; Leny Suzan; Dewa PK. Mahardika (Jurusan Akuntansi Politeknik Negeri Bandung, 2016)
Abstract: Indonesian banks have a primary function as a collector and distributor of public funds. In collecting funds from the public, the bank offers some savings instrument and in channeling funds to the public, banks give it in various loan form. The purpose of this research is to find out the effect of third-party funds, BI rate and BOPO on the bank loan, either simultaneously or partially. This research is descriptive verification and causality research. The object that used in this research is the BUMN banks that listed in Indonesian Stock Exchange. The sample of this research is 4 banks during five years, from 2011 to 2015. This research using panel data regression analysis technique. The result of this research shows that simultaneously, third-party funds, BI rate, and BOPO have effect on bank loan. Partially, third-party funds and BI rate have positive effect on bank lending, while BOPO has no effect on bank loan. Keywords: Third-Party Funds, BI Rate, BOPO, Bank Loan